Identification and Retrieval of WWW-based Courseware: A Metadata Approach - Kenny, Sarah Anne (Trinity College Dublin. Department of Computer Science, 1999)
Information retrieval is often a tedious and time consuming task on the Internet, as information is stored in an unstructured manner. There is no guarantee that what you find is relevant to your needs, on the correct topics, up to date or written by a reliable source. In the educational domain, the focus has shifted towards an ongoing training process, where a lifelong education is required. The Web provides an ideal medium for the delivery of distance education and online courses if the resources could be found. There is a need for an agency or broker to provide a search and retrieval service for educational information. This dissertation concerns itself with educational resources and the problems of identification and retrieval of educational resources on the World Wide Web. It intends to investigate the approaches and technologies used for the description of educational resources and to develop a suitable architecture. it will examine how information is currently represented on the World Wide web with reference to the emerging educational standards. It will investigate the technologies used to represent educational resources with an in-depth look at the use of XML. The technology of search engines and intelligent agents will be analysed to evaluate their information retrieval methods.
Keywords: Computer Science